2015
DOI: 10.3390/ijerph121013118
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Legionella Contamination in Bath Water Samples by Culture, Amoebic Co-Culture, and Real-Time Quantitative PCR Methods

Abstract: We investigated Legionella contamination in bath water samples, collected from 68 bathing facilities in Japan, by culture, culture with amoebic co-culture, real-time quantitative PCR (qPCR), and real-time qPCR with amoebic co-culture. Using the conventional culture method, Legionella pneumophila was detected in 11 samples (11/68, 16.2%). Contrary to our expectation, the culture method with the amoebic co-culture technique did not increase the detection rate of Legionella (4/68, 5.9%). In contrast, a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…Some studies have detected the presence of Legionella bacteria in hot water supply systems [6][7][8][9]. One study also found that there was Legionella bacteria in a filled tub in a Japanese bathing facility.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have detected the presence of Legionella bacteria in hot water supply systems [6][7][8][9]. One study also found that there was Legionella bacteria in a filled tub in a Japanese bathing facility.…”
Section: Introductionmentioning
confidence: 99%
“…9 In other study, more than 1100 cases of legionellosis in Japan, caused by contaminated artificial whirlpool spas or natural hot springs were presented in Infectious Agents Surveillance Report 2014. 10 Only a few factors have been detected and characterized that contribute to survival of the L. pneumophila in eukaryotic cells. The macrophage infectivity potentiator (mip) gene is described as a virulence factor necessary for optimal intracellular survival of this bacterium.…”
mentioning
confidence: 99%
“…Real Time PCR can also determine the presence of non-cultivable Legionella spp., especially VBNC types [15]. Our results have shown that real-time PCR was more sensitive and less time consuming to detect the L. pneumophilia in water samples.…”
Section: Discussion Of Resultsmentioning
confidence: 62%